Voltaire and the triumph of the Enlightenment - Kors, Alan Charles (Chantilly, VA The Teaching Co., 2001)
Alan Kors, a professor at the University of Pennsylvania, delivers lectures on the life and times of the French philosopher Voltaire.
lecture 1. The patriarch, an overview -- lecture 2. The education of a philosophe -- lecture 3. Philosophical letters, part I -- lecture 4. Philosophical letters, part II -- lecture 5. The years at Cirey -- lecture 6. From optimism to humanism -- lecture 7. Voltaire and the "philosophical tale" -- lecture 8. Voltaire at Ferney -- lecture 9. Voltaire and God -- lecture 10. Voltaire and history -- lecture 11. Voltaire and toleration -- lecture 12. Apotheosis.
In container (23 cm.).
Keywords: Voltaire -- 1694-1778 -- Criticism and interpretation; Philosophy, Modern -- History